2021
DOI: 10.1109/access.2021.3051367
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Entropy Analysis of Instantaneous Frequency Variation to Overcome the Cross-Over Artifact in Rhythmic EEG

Abstract: Generally, for healthy adults, the entropy of electroencephalogram (EEG) signals gradually decreases from wake to sleep stages N1, N2, to N3, and increases during REM. However, some researchers found that multiscale entropy curves of sleep and wakefulness intercept, a cross-over phenomenon whose origin remains unexplored. The objective of the present work is to trace the origin of the cross-over phenomenon and to propose a workaround strategy. We simulated EEG by generating 1/f broadband signal and chirp signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Alpha peak frequency varies constantly, and the variation does not represent random fluctuations but instead constitutes the basis of an adaptive mechanism mirroring the activation level of neural populations (Mierau et al, 2017 ). Previously, we have shown that the EEG alpha rhythm changes its peak frequency constantly and the MSE analysis of the instantaneous frequency variation (IVF) can be used to show the complexity loss of the brain in sleep comparing to in wakefulness (Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Alpha peak frequency varies constantly, and the variation does not represent random fluctuations but instead constitutes the basis of an adaptive mechanism mirroring the activation level of neural populations (Mierau et al, 2017 ). Previously, we have shown that the EEG alpha rhythm changes its peak frequency constantly and the MSE analysis of the instantaneous frequency variation (IVF) can be used to show the complexity loss of the brain in sleep comparing to in wakefulness (Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Li et al ( 2021 )'s work, the reason for using MSE analysis on IFV in spontaneous alpha rhythm or delta wave instead of on the brain wave itself is that the MSE algorithm suffers from the artifact of the carrying frequency of the brain waves. In this study, we have also shown the IFV in alpha rhythm either from spontaneous EEG or from ASSR has much higher separation power.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations